Synthesis and analysis of the Early to Middle Holocene radiocarbon record for the Northern Northwest Coast of North America: A gap in dated components between ∼9000 and 8300 cal BP. (2nd October 2021) - Brown, Thomas J.; Ames, Kenneth M.
Abstract: The Northern Northwest Coast of North America has consistently been an epicenter of hunter-gatherer research, but attention has focused on the period after 5000 cal BP. Using data largely produced within the past 12 years, we present the first synthesis and analysis of this region's 14 C record between ∼11000 and 5000 cal BP. Our analysis produced two primary findings (i) that the number of dated sites does not increase or decrease significantly during this period and (ii) there is an unexplained gap in dated sites across the entire region between ∼9000 and 8300 cal BP. The existence of this gap has critical implications regarding hypotheses of technological change, migration, population continuity, and cultural evolution for the region. However, available explanations for this gap are problematic. Possible causes investigated include: demographic abandonment of the region, distorting effects of the calibration curve, sea-level change, taphonomy, and sampling error. All are found to be inadequate.